Physiotherapy students' and officers' knowledge, attitudes, and perceptions of mental health - Marilyn Hooblaul; Oladapo M. Olagbegi; Thayananthee Nadasan (AOSIS, 2024)
Background: Physiotherapy in mental health is not very popular among physiotherapists, students, healthcare professionals, and people living with mental illness (PLWMI), although many PLWMI are managed by physiotherapy students and physiotherapists. Aim: This study aimed to determine the knowledge, attitudes, and perceptions of physiotherapy students and physiotherapy community service officers (PCSOs) towards mental health. Setting: The study was conducted in KwaZulu-Natal (KZN). Methods: A concurrent mixed-method was employed using the Attitudes Toward Psychiatry (ATP-30) questionnaire and focus group discussions. The questionnaire was distributed to 100 PCSOs and 191 physiotherapy students. Focus groups were conducted to assess the knowledge gained through the undergraduate programme, comprising three groups of students from second to fourth year and two groups of PCSOs. An interview was also conducted with one PCSO. Results: A total of 146 students and 72 community service officers completed the questionnaire. Participants had an overall positive attitude, with a mean ATP-30 score of 108.02 (standard deviation [s.d.] = 10.86). Those with a family member or friend with a mental illness scored higher. Focus groups revealed limited knowledge about mental health and reluctance to work in the field. Conclusion: Physiotherapy students and PCSOs in KZN had positive attitudes towards mental health despite limited knowledge. They expressed a desire for more information about mental health. Contribution: The curriculum needs to include adequate mental health content to prepare students to manage PLWMI after graduation, reducing stigma, and negative perceptions, and ensuring confidence.